STRATEGI KESANTUNAN BERBAHASA POSITIF-NEGATIF PADA KOMUNIKASI MAHASISWA DENGAN DOSEN DALAM KONTEN TIKTOK KREATOR @DOSENTRAVELER - Nurfaadiyah Rahmi; Muhammad Saleh; Sakinah Fitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is a descriptive study with a qualitative approach that aims to describe the positive and negative language politeness strategies used by students when communicating with lecturers in TikTok content creator @dosentraveler. The data sources in this study are twenty-eight contents from TikTok creator @dosentraveler published in 2024 to 2025. The results of this study indicate that students use fifteen positive language politeness strategies from Brown and Levinson's theory, some of which are predominantly used, namely paying attention to the likes, desires, and needs of the interlocutor, showing speech that has the same perception as the interlocutor, showing the speaker's understanding of the interlocutor's desires, and giving gifts. Meanwhile, students also use ten negative language politeness strategies from Brown and Levinson's theory, some of which are predominantly used, namely minimizing coercion and giving respect.